2008
DOI: 10.1152/ajpregu.00435.2007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic activation of plasma renin is log-linearly related to dietary sodium and eliminates natriuresis in response to a pulse change in total body sodium

Abstract: Responses to acute sodium loading depend on the load and on the level of chronic sodium intake. To test the hypothesis that an acute step increase in total body sodium (TBS) elicits a natriuretic response, which is dependent on the chronic level of TBS, we measured the effects of a bolus of NaCl during different low-sodium diets spanning a 25-fold change in sodium intake on elements of the renin-angiotensin-aldosterone system (RAAS) and on natriuresis. To custom-made, low-sodium chow (0.003%), NaCl was added t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Recently, it was found that sodium intake determines the activity of the renin system in a log-linear fashion (441). The salt-dependent changes in the RAAS activity have been suggested to be mediated by 1) systemic humoral factors, 2) intrarenal factors, 3) renal nerves, or 4) the intrarenal MD mechanism.…”
Section: B Salt Intakementioning
confidence: 99%
“…Recently, it was found that sodium intake determines the activity of the renin system in a log-linear fashion (441). The salt-dependent changes in the RAAS activity have been suggested to be mediated by 1) systemic humoral factors, 2) intrarenal factors, 3) renal nerves, or 4) the intrarenal MD mechanism.…”
Section: B Salt Intakementioning
confidence: 99%
“…The plasma renin concentration (PRC) is log-linearly related to salt intake in humans, rats, and dogs; however, the slopes of the relationships differ [23,53,64], indicating that the salt sensitivity of the renin system differs between species. Moreover, when the results of studies in different species are compared, it should be considered that the salt intake of a rat consuming a normal laboratory diet is approximately tenfold higher than that of dogs or humans, and this intake is at the upper end of the operational range of the salt-dependent regulation of renin release [23].…”
Section: Introductionmentioning
confidence: 99%
“…In conscious dogs, a linear relationship between PRC and the logarithm of steady‐state sodium intake has been found (Kjolby et al . , Kjolby & Bie ). Similar log‐linear relationships were found for angiotensin II (ANG II) and aldosterone (Kjolby & Bie ).…”
mentioning
confidence: 96%
“…, Kjolby & Bie ). Similar log‐linear relationships were found for angiotensin II (ANG II) and aldosterone (Kjolby & Bie ). Sodium‐mediated deactivation of the RAAS occurred without changes in MABP and heart rate (HR) with a small but significant increase in plasma volume (Kjolby et al .…”
mentioning
confidence: 96%